APPLICATION OF THE TRIPLE BOTTOM LINE IN INTEGRATED FINANCIAL REPORTS IN THE AUTOMOTIVE INDUSTRY - Elmiano A.E. Erong; Marcella T. Abur, Ahmad Q. Izzuddin, Maria Yovita R. Pandin (Adisam Publisher, 2024)
The aim of this research is to determine the application of the Triple Bottom Line (people, profit, planet) in integrated financial reports in the automotive industry listed on the IDX. The type of research carried out was qualitative with secondary data sources obtained from the Indonesian Stock Exchange and other sources. The population in this research is automotive companies listed on the Indonesia Stock Exchange, totaling 11 companies. There were 6 companies in the sample with certain criteria. Data analysis based on the triple bottom line concept. The research results show that when applying the triple bottom line with the Profit indicator, the company that has the highest profit in 2021-2023 as measured by the net profit margin is PT. Multi Prima Sejahtera in 2021 with a ratio of 0.20 and PT Selamat Selamat in 2022 and 2023 with a ratio of 0.19 and 0.20. Meanwhile, from People's point of view, PT Indo Kordsa with an employee salary growth rate of 0.212 in 2021 is the company that pays the most attention to employee salaries compared to the other five companies. Meanwhile, in 2022 it will be PT Multi Prima Sejahtera with a growth rate of 0.390 and in 2023 it will be PT Astra International with a growth rate of 0.153. Meanwhile, from the Planet indicators, the company that pays the most attention to the environment in 2021-2023 as measured by the environmental cost ratio or the ratio of environmental costs to net profit is PT Indo Kordsa with a ratio of 0.0176 in 2021, 0.0098 in 2022 and 0 .0390 in 2023.